Genomics and transcriptomics to protect rice (Oryza sativa. L.) from abiotic stressors: -pathways to achieving zero hunger - Ahmad, Mushtaq (Frontiers in Plant Science, 2022)
More over half of the world's population depends on Rice (Oryza Sativa., L.) as a major food crop. Rice is vulnerable to abiotic challenges including drought, cold, and salinity since it is grown in semi-aquatic, tropical, or subtropical settings. Abiotic stress resistance has been bred into rice plants since the earliest rice cultivation techniques. Prior to the discovery of the genome, abiotic stress-related genes were identified using forward genetic methods, and abiotic stress-tolerant lines were developed using traditional breeding methods. Dynamic transcriptome expression represents the degree of gene expression in a specific cell, tissue, or organ of an individual organism at a specific point in its growth and development. Transcriptomics can reveal the expression at the entire genome level during stressful conditions from the entire transcriptional level, which can be helpful in understanding the intricate regulatory network relating to the stress tolerance and adaptability of plants. Rice gene families can be found comparatively using the reference genome sequences of other plant species, allowing for genome-wide identification. Transcriptomics via gene expression profiling, which has recently been dominated by RNA-Seq, complements genomic techniques. The identification of numerous important QTLs, genes, promoter elements, transcription factors, and miRNAs involved in rice's response to abiotic stress was made possible by all of these genomic and transcriptomic techniques. The use of several genomes and transcriptome methodologies to comprehend rice's ability to withstand abiotic stress has been discussed in this review